Evaluation of salivary Chemerin in oral leukoplakia, oral squamous cell carcinoma and healthy controls - Karthika Pradeep Susha; Rathy Ravindran (Wolters Kluwer Medknow Publications, 2023)
Introduction: Chemerin is a multifunctional chemoattractant cytokine, encoded by RARRES2 gene. Its role in oral carcinogenesis is largely unexplored. Study was undertaken to evaluate the role of salivary chemerin as a potential biomarker in the early diagnosis of oral cancer and to elucidate the clinicopathologic and prognostic significance of chemerin in different grades of Oral Squamous Cell Carcinoma (OSCC) and oral leukoplakia. Materials and Methods: The study comprised 96 subjects, divided into 3 groups, each consisting of 32 subjects. These groups were clinically and histopathologically diagnosed with OSCC, oral leukoplakia, and healthy controls, respectively. The whole unstimulated saliva (1.5 mL) was collected from the subjects using passive drool technique and immediately centrifuged at 3000 rpm for 10 minutes. The salivary chemerin level was estimated using the competitive sandwich enzyme-linked immunosorbent assay method. The statistical analysis was performed using R software EZR version 1.32. Independent t-tests, analysis of variance tests, and Scheffe Multiple Comparisons were carried out to compare quantitative parameters. A receiver operating characteristic (ROC) curve was plotted to assess diagnostic accuracy of salivary chemerin. Results: Significantly higher levels of salivary chemerin were observed in OSCC and oral leukoplakia patients compared to healthy controls (P < 0.05). The study further established an increase in salivary chemerin concentration in different histological grades of OSCC and oral leukoplakia. ROC curve analysis suggested that salivary chemerin is a highly sensitive and specific indicator for early screening and detection of oral leukoplakia and OSCC. Conclusion: Salivary chemerin can be considered as a reliable and specific indicator for the early screening and detection of oral leukoplakia and OSCC and a highly sensitive biomarker which may aid in detection of malignant transformation of oral leukoplakia.